The effect of lactation counselling by telephone on breastfeeding practices among mothers who attended a public hospital in Kuala Lumpur, Malaysia / Norzakiah Mohd Tahir - Norzakiah , Mohd Tahir (2016)
The exclusive breastfeeding rate at four month in Malaysia has declined from 29.0% in 1996 to 19.3% in 2006, despite the implementation of the National Breastfeeding Policy and the Baby Friendly Hospital Initiative policy in government hospitals since 1993. This thesis research assessed the effects of pro-active lactation counselling provided through telephone among mothers who gave birth in a public hospital in Kuala Lumpur. Two study designs were conducted to achieve the objective of this thesis. A randomized controlled trial was conducted whereby provider-initiated telephone lactation counselling by nursing professionals was rendered twice monthly for six months to mothers who had the intention to breastfeed their newborn infants. This intervention was effective in increasing the exclusive breastfeeding rate at the first month postpartum (intervention vs. control: 84.3% vs. 74.7%, OR 1.83 95% C.I. = 1.05, 3.16) but not at the later postpartum months. The intervention was well accepted by the mothers, found to be helpful, improved the mother’s satisfaction with breastfeeding and the mother’s sense of comfort with breastfeeding. A qualitative study explored the Lactation Counsellor’s opinion on the intervention found that the greatest determinant which affected the provision of telephone-based lactation counselling was the intention of Lactation Counsellors, followed by external constraints. Mothers’ influence and behaviour also played an apparent role in the success of telephone counselling. In conclusion, this research has shown the promising effects of telephone lactation counselling in increasing the exclusive breastfeeding practice, particularly in the early postpartum months. Future research need to iv focus on providing extensive support module at the early postpartum period, among mothers who has higher risk of stopping breastfeeding.